The Effects of Moisture Content and Temperature on the Storability of an Orthodox, Intermediate and a Recalcitrant Forest Tree Seed - Nadarajan, Jayanthi (1999)
The effects of seed moisture and storage temperature on storability of an orthodox (Instia palembanica), an intermediate (Swietenia macrophylla) and a recalcitrant (Hopea odorata) forest tree seed were studied. The objectives were to determine the critical and optimum moisture and storage temperature for storage of each of the three species, and to evaluate the potential of these seeds for cryopreservation at ultra-low temperatures of liquid nitrogen. The study was divided into four parts of three experiments, each being for one of the three species. In Part I, the effects of desiccation on seed viability were evaluated. The orthodox seed, I. palembanica, has low shedding moisture of 10%. It was tolerant to desiccation as its critical and optimum moistures were low at 6% and 8-10% respectively. For the intermediate seed, S. macrophylla, it was more sensitive to desiccation. Its shedding moisture was high at 37% and it could not withstand excessive desiccation as its critical and optimum moistures were high at 1 5% and 25% respectively. The recalcitrant seed, H. odorata, has very high shedding moisture of 48% and was highly sensitive to even slight desiccation. Its critical and optimum moistures were very high at 29% and 32-35% respectively.